Polioviral receptor binding ligand: A novel and safe peptide drug carrier from polioviral capsid - Jiradej Manosroi (2018)
Cellular uptake enhancement of green fluorescent protein (GFP) into human colon adenocarcinoma (HT-29) and human mouth epidermal carcinoma (KB) cells by a segment of VP1-BC loop polioviral capsid (V), a polioviral receptor binding peptide and HIV-I transactivator of transcription (Tat) was evaluated. HT-29 and KB cells were incubated with various molar concentrations of GFP, V, and Tat mixtures. Both V and Tat showed potent enhancement of GFP uptake into HT-29 and KB cells. In HT-29 cells, the V-GFP, Tat-GFP, and V-Tat-GFP mixtures enhanced the GFP cellular uptake efficiency with the maximum of 3.98-, 4.59-, and 4.08-folds of GFP at 1:3, 1:1/6, and 1/6:1:1/6 molar ratios, respectively. For KB cells, the V-GFP, Tat-GFP, and V-Tat-GFP mixtures enhanced the GFP cellular uptake efficiency with the maximum of 4.05-, 5.09-, and 4.91-folds of GFP at 1:1/6, 1:1, and 1:1:1 molar ratios, respectively. Both V and V-GFP mixtures showed a lower cytotoxicity effect than Tat and Tat-GFP mixture. These studies demonstrated the potential of polioviral capsid, a polioviral receptor binding peptide as a novel, low cytotoxicity carrier for the development of peptide drugs delivery system. © 2012 Informa Healthcare USA, Inc.